Note: Gratings on low absorbing substrates for x-ray phase contrast imaging - Koch, F. J.; Schroeter, T. J.; Kunka, Danays; Meyer, Pascal Edouard; Meiser, J.; Faisal, A.; Khalil, M. I.; Birnbacher, L.; Viermetz, M.; Walter, M.; Schulz, Joachim; Pfeiffer, F.; et al. (Review of Scientific Instruments, 2015)
Grating based X-ray phase contrast imaging is on the verge of being applied in clinical settings. To achieve this goal, compact setups with high sensitivity and dose efficiency are necessary. Both can be increased by eliminating unwanted absorption in the beam path, which is mainly due to the grating substrates. Fabrication of gratings via deep X-ray lithography can address this issue by replacing the commonly used silicon substrate with materials with lower X-ray absorption that fulfill certain boundary conditions. Gratings were produced on both graphite and polymer substrates without compromising on structure quality. These gratings were tested in a three-grating setup with a source operated at 40 kVp and lead to an increase in the detector photon count rate of almost a factor of 4 compared to a set of gratings on silicon substrates. As the visibility was hardly affected, this corresponds to a significant increase in sensitivity and therefore dose efficiency.
CRIS-Team Scopus Importer:2023-03-08